Spatio-temporal Identification of Regions with Anomalous Values of 222 Rn in Groundwater of Madurai District, Tamilnadu, India - Thivya, C.; Chidambaram, S.; Thilagavathi, R.; Prasanna, Mohan Viswanathan; Nepolian, M.; Tirumalesh, K.; Noble, J. (Springer International Publishing, 2014)
Measurement of dissolved radon (222 Rn) activity concentration in groundwater samples from private and public hand pumps, and in bore wells located at Madurai district of Tamilnadu, India, are presented. The study attempts to identify the background value of 222 Rn in groundwater of hard rock terrain and the main aquifer contributing 222 Rn, and to determine if any correlation exists with observed field parameters. Measured parameters included pH, TDS, Temperature and 222 Rn in 42 samples for two seasons (South West Monsoon [SWM] and North East Monsoon [NEM]). The results show that the 222 Rn activity concentration of the samples ranged from 0.049 to 59.952 Bq/L in South west monsoon and 0.12 to 211.60 Bq/L in North east monsoon. The higher activity was noted in NEM and the highest 222 Rn concentrations were observed in granitic terrains in both seasons. The average values of the parameters studied shows that there is a general decrease of TDS and Temperature, but an increase in 222 Rn and pH during NEM. The spatial representation of the activity shows that maximum values are in the north eastern part of the study area. Further, correlations between the measured parameters show that temperature has a negative correlation to the samples of charnockite formation during both seasons; pH and TDS also show negative relationships to 222 Rn during SWM.